Zn2SnO4-carbon cloth freestanding flexible anodes for high-performance lithium-ion batteries. (15th October 2018) - Xia, Ji; Tian, Ran; Guo, Yiping; Du, Qi; Dong, Wen; Guo, Runjiang; Fu, Xiuwu; Guan, Lin; Liu, Hezhou
Abstract: Zn2 SnO4 -carbon cloth, prepared via the coherent growth of Zn2 SnO4 on pre-functionalized carbon cloth, was employed as a freestanding and binder-free anode for lithium-ion batteries. The 2D Zn2 SnO4 nano-plates were uniformly anchored on the surface of 1D carbon cloth to form a hierarchical structure, providing the fast Li-ion and electron exchange path and reducing the volume change during the Li-ion planting/stripping. The binder-free electrode delivered significantly enhanced electrochemical performance by maintaining a reversible capacity of 1510 mA h/g after 60 discharge-charge cycles at a current density of 100 mA/g compared with that of the Zn2 SnO4 . Systematic structural and electrochemical characterizations suggested that the synergistic effect between Zn2 SnO4 nanoplates and carbon cloth was responsible for the high electrochemical performance. Therefore, this study would be of significance for promoting the application of binary transition metal oxides in lithium-ion batteries. Graphical abstract: Highlights: Zn2 SnO4 -carbon cloth freestanding flexible anodes have been successfully prepared. The hierarchical structure provides the fast Li-ion and electron exchange path. The reversible capacity can keep at 1510 mA h/g after 60 discharge-charge cycles. The flexible electrode delivers 536 mA h/g at current density of 1000 mA/g. Synergistic effect between Zn2 SnO4 and carbon greatly enhanced performance of battery.